Socioeconomic impact of COVID‐19 pandemic: Evidence from rural mountain community in Pakistan. Issue 4 (24th August 2020) - Ali, Amjad; Ahmed, Mumtaz; Hassan, Nazia
Abstract : This study examines the trend of the spread of coronavirus disease (COVID‐19) pandemic in Pakistan and to explore the community perception of the socioeconomic impact of COVID‐19 pandemic in a rural mountain area of Pakistan. An online survey was conducted through snowball sampling technique and total 367 people participated in the survey. The results of the study show that COVID‐19 cases spiked amid ease of lockdown in the country and the spread of novel coronavirus pandemic has significant socioeconomic impact on the lives of mountain communities in Gilgit‐Baltistan. Financial uncertainty, decrease in income, fear of job loss, and food insecurity are some major challenges that mountain communities face due to outbreak of coronavirus in the region. The results further show that lack of community cooperation with government agencies, lack of awareness about the severity of coronavirus, and insufficient COVID‐19 testing kits are the major factors that caused the spread of coronavirus cases. This study suggests that the short‐, medium‐, and long‐term policies are required to mitigate the consequences of this pandemic and to revitalize the mountain economy of Gilgit‐Baltistan, and in this regard, this study provides baseline information for policy‐makers and practitioners to devise such demanding policies.